The optimum level of reserves in an exchange rate target zone - Hurley, Margaret; McCormack, Pat; O'Brien, Stuart (Economic & Social Studies, 1993)
The target zone exchange rate literature, initiated by Krugman (1991), has relevance for the question of what is the optimal level of reserves. In particular, Krugman and Rotemberg (1990) show that there is a well defmed boundary between a target zone that is subject to speculative attack and one which is sustainable. This boundary is defined by whether reserves are sufficient or not. This paper reviews briefly both the target zone and speculative attack literature. The appropriate level of reserves for Ireland is then calculated and discussed.
Keywords: Exchange rates; Reserves; Target zones